Задоволення освітніх потреб української національної меншини в Польщі та польської національної меншини в Україні: проблеми, здобутки, перспективи - Стрільчук, Людмила Василівна; Strilchuk, Liudmyla V. (Волинський національний університет імені Лесі Українки, 2012)
У статті досліджено українську національну меншину в Польщі та польську національну меншину в Україні в процесі налагодження системи національної освіти. Україна та Польща всіляко підтримують розвиток освіти національних меншин. Цьому сприяє законодавча база обох країн. Упродовж двох останніх десятиріч національні меншини створили та різносторонньо розвинули мережу освітніх закладів та установ, які сприяють задоволенню їхніх освітніх потреб.

This article investigates the Ukrainian minority in Poland and the Polish minority in Ukraine in the process of establishing a system of national education. Ukraine and Poland strongly support the development of minority education, and this contributes to the legal framework of both countries. Over the past two decades, national minorities established and multi-task network of educational institutions and organizations that contribute to the educational needs of minorities.
A to Meet the Educational Needs of the Ukrainian Minority in Poland and the Polish Minority in Ukraine: Problems, Achievements and Prospects
Keywords: національна меншина; освіта; Україна; Польща; співпраця; українці; поляки; державна підтримка; освіта; minority education; Ukraine; Poland; cooperation; Ukrainian; Polish; government support